(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The authors propose that the G20 concentrate on sustainable construction SMEs as a method to boost financial de-risking while satisfying the Paris Agreement’s promises and the United Nations Sustainable Development Goals. And according to G20/OECD Higher Levels of motivation of SMEs Financing, SMEs, comprising small - angle x, are vital engines of entrepreneurship, investment, business growth, and empowerment in viable options as well as moderate emerging nations. This should be actually achieved by timely manner for international investment through: (1) an investigating structure that enables monitor the scale-up of green-technology SMEs; (2) the use of taxpayer resources to signal application of green SMEs to investment firms; and (3) the involvement of SMEs inside this prototype of carbon trading platforms. The G20 will ensure that modern, low-carbon SMEs becomes appealing, low-risk economic opportunities for the corporate companies by adopting these suggestions.